PWE-004 Diagnostic Accuracy of Magnetic Resonance Enterography in Detecting Small Bowel Crohn's Disease – Relationships with Faecal Calprotectin. (17th August 2016) - Nelson, A; Oka, P; Petty, D; Wilkinson, C; Kant, P
Abstract : Introduction: Around one third of patients with Crohn's disease (CD) have isolated small bowel involvement at diagnosis. Magnetic resonance enterography (MRE) is a recognised tool for identifying small bowel disease. Faecal calprotectin (FCp) is a marker to help differentiate functional from organic gastrointestinal symptoms and is typically elevated in CD. This study aims to determine the diagnostic accuracy of MRE in patients with symptoms suspicious for CD and assess the relationship between FCp and presence of small bowel disease on MRE. Methods: Patients with suspicion for CD who underwent MRE over a 23 month period (Jan 2013 to Nov 2014) were identified using a local database. All study patients had undergone a normal colonoscopy to exclude Crohn's colitis. MRE reports were reviewed for evidence of small bowel abnormalities, and whether these were likely to represent CD. FCp levels (μg/g) from 3 months preceding MRE were recorded. Casenote review revealed outcome and patient disposition at 1 year post-MRE. Results: In total 73 patients underwent MRE (mean age 37.5; range 13–77; 46:27 female:male). 3 had MRE findings radiologically diagnostic for CD, their FCp ranged from 389 to 600. 19/73 patients had MRE features of non specific ileitis with corresponding median FCp level of 222 (inter-quartile range [IQR] 71–600). At 1 year a further of 3 of these 19 patients (FCp range 294–600) were positively diagnosed as CD. Of the remaining 16 with non specific ileitis on MRE, none had CD at 1 year. In this sub-group the median FCp was 139 (45–517), 5 had a normal capsule endoscopy, 12 had functional pain, 3 had infectious ileitis, and 1 was lost to follow-up. The majority of patients however (51/73 [69.9%]) had normal MRE with a median FCp of 142 (83–416) and none had CD at 1 year. Median differences in the FCp value between those with normal and abnormal MRE were apparent but not statistically significant (p = 0.42). Overall sensitivity of MRE in diagnosing small bowel involvement is high at 100% as is a negative predictive value of 100% although we acknowledge the small sample size. Within the group reported as indeterminate Ileitis only 3/19 were subsequently diagnosed with Crohn's disease. Conclusion: MRE excels in excluding small bowel CD in suspected patients and is reliable when positively diagnosing Crohn's. In early Crohn's disease there is uncertainty in differentiating the radiological appearances with other causes of ileitis. These data support the development of an appropriate threshold for abnormal FCp as a screening tool to improve MRE accuracy. This could reduce the number of unnecessary MRE examinations without missing any cases of small bowel CD. Disclosure of Interest: None Declared